Settlement of Non-Performing Lending in Sharia Banking Through KPKNL Surabaya from The Perspective of Islamic Law - Sulistyowati, Sulistyowati (Al-Daulah: Jurnal Hukum dan Perundangan Islam, 2021)
In the face of non-performing lending caused by the absence of potential for recovery of the condition of Islamic Bank customers, the next strategy that can be carried out is through the disbursement of collateral to cover the customer's obligations. This strategy can be carried out with the help of related institutions such as institutions in charge of administering auctions, to resolve this problematic financing. Through KPKNL, customers voluntarily provide collateral and are assisted by the Bank to settle their obligations. However, if the opposite condition occurs, where there is no good faith from the customer, litigation can be taken to settle the customer's obligations. This litigation process takes place in court. In general, a warning letter will be given 3 times, if the customer does not pay attention, then it will be processed through the KPKNL. The auction procedure through the KPKNL will be discussed in this study, including the auction procedure for the object of this research. The analysis conducted by the research shows that the auction process through the KPKNL is as per the provisions and Islamic law regarding the sale and purchase of an object. However, the researchers found a discrepancy with Islamic law regarding the acquisition of auction objects derived from illegal seizure or looting. That is, no valid documents come with the object for auction. Therefore, it contravenes the principle of Islam in the Qur'an.